Migraine in Medicine A Machine-Generated Overview of Current Research - Martelletti, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book on migraine is the first machine-generated scientific book in medicine published by Springer Nature, and reflects a new publication format which focuses on literature reviews: state-of-the-art computer algorithms were applied to select relevant sources from Springer Nature journal articles, rearrange them in a topical order, and provide short summaries of these articles. The result is the auto-summarization of current texts, organized by means of a similarity-based clustering routine in coherent chapters and sections. The human intervention of a world-renowned expert in this field grants the scientific soundness and appropriate organization of the contents identified. The AI-based approach seemed especially suitable to provide an innovative perspective as the topics are indeed both complex, interdisciplinary and multidisciplinary, as is migraine, the most important among the chronic non communicable diseases under the age of 50s. The result of this innovative process will be of help especially for readers with limited time, interested in migraine and wishing to learn more about the subject quickly and particularly if they are new to the topic. Springer Nature seeks to support anyone who needs a fast and effective start in their content discovery journey: from the undergraduate student exploring interdisciplinary content, to Master or PhD-thesis developing research questions, to the practitioner seeking support materials, this book can serve as an inspiration, to name a few examples. .
Public Health: Epidemiology -- Personal and Societal Impact -- Economics of Migraine -- Governance of Headache Centers. Mechanisms: Genetics -- Biology -- Comorbidities.Lifestyle -- Hormones -- Drug-Drug Interactions. Diagnosis: Classification -- Medical History -- Medication Overuse -- Differential Diagnosis -- Diagnostic Tools: Treatment: Guidelines -- Acute -- Preventive -- Non-pharmacological -- Invasive and non-invasive neuromodulation -- Emergency Management -- Pregnancy -- Childhood and Adolescent -- Elderly -- Outcome Measures and Algorithms -- Infrequent Migraine subtypes. Future Research Directions: Brain Traumas Brain Traumas -- Post-CoVID Epidemiology -- New drugs.
Keywords: Internal medicine; Public health; Internal Medicine; Public Health; Migraine Disorders